Capital Structure Management of Joint Venture Banks of Nepal - Timsina, Sujata (Journal of Business and Social Sciences Research, 2018)
This study entitled,” Capital Structure Management of Joint Venture Banks of Nepal” has been conducted to examine whether the determinants of capital structure affect the leverage position of joint venture banks. Three joint venture banks have been selected for the study based on their similarities in assets size and age. The study intends to test the relationship between capital structure and profitability and evaluate the optimality of the capital structure of the banks. The main purpose of this study is to analyze and compare the capital structure management practices of three leading joint venture banks taken into consideration.This study has been conducted with the secondary data obtained from the quarterly financial statements, annual publications of NRB and even from the official website of Nepal Stock Exchange. A linear regression model has been applied for analyzing the data. Six independent variables have been identified based on the standard determinants of capital structure. The variables include size, profitability, assets tangibility, liquidity, risk and growth. To determine the variables, previous studies particularly of Sailaja and Madhavi (2015), Singh and Tandon (2012) and Basnet (2015) have been consulted. Statistical and financial tools such as ratio analysis, correlation and regression analysis as well as inferential analysis have been used to analyze the quantitative data.The researcher has been able to draw the conclusion that the regulatory requirements also affect the leverage position. In addition to these, factors that are significant to the capital structure of the three sample banks are size of the bank, profitability, liquidity and growth. The study has thus helped to find out strengths & weaknesses of the joint venture banks. With these findings, the study might be helpful to drive the banks into the progressive track. Understanding these factors and their crucial relationships with leverage will help to maximize the value of the bank and minimize the overall cost of capital.The study concludes that amongst the three joint venture banks taken into consideration, Everest Bank Limited is the better in terms of profitability, Himalayan Bank Limited is better in terms of stability and Nepal SBI Bank is more risk prone but has sufficient liquidity. Hence, the study shows that the standard determinants of capital structure are actually able to explain the variation in leverage of banks.Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 58-79